MORPHOLOGICAL AND AGRONOMIC TRAITS OF WHEAT GENOTYPES INFLUENCED BY PLANTING DATES - Khalil, S. K.; Rehman, A.; khan, A. Z.; Akhtar, S.; Khalil, I. H.; Rehman, S. (The Nucleus, 2020)
Number of leaves and specific leaf area are important traits affecting physiological processes including photosynthate production, assimilate accumulation and partitioning. Wheat planted later than optimum-planting time usually reduces leaves per plant and other parameters. The objective of this study was to quantify the reduction in leaf traits and grains per spike of wheat varieties if planting is delayed. Three wheat varieties (Bakhtawar-92, Inqulab-91, and BNS) were planted on six dates from October 15 to December 30 with 15 days interval at New Developmental Farm, Agricultural University Peshawar, Pakistan. Planting date and varieties significantly affected number of leaves per plant, leaf weight, specific leaf weight, days to maturity and number of grains per spike. Wheat planted on October 15 produced heavier leaves and took maximum days to maturity, while leaves per plant increased upto October 30 planting. Specific leaf area and number of grains per spike increased up to November 30, thereafter both parameters decreased. Variety Bakhtawar-92 and BNS took more days to maturity; produced more leaves per plant, specific leaf area and more grains per spike. It can be concluded that all the three varieties can be planted upto 30th November as it produced more grains per spike and specific leaf area, however, leaves per plant increased upto October 30, thereafter no increase was observed in Peshawar valley, NWFP, Pakistan.